PENGARUH KOMUNIKASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT RUMAH SAKIT ERIA PEKANBARU - Sinaga Gratia; Sasmita Jumiati; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine The Influence of Communication, OrganizationalCulture and Work Environment to Performance of Nurses at Eria HospitalPekanbaru. The population in this study includes the Nurses at Eria HospitalPekanbaru, totaling 73 people. Primary data was collected by questionnaire as aninstrument to prove the results of the research and secondary data was collectedthrough observation, literature study and interview with the parties involved in thisresearch. To test the hyphotesis in this study is using multiple linear regressionanalysis with SPSS 25 (Statistical Program for Social Sciences). The samplingtechnique that has been selected is Saturated Sample (73 Nurses at Eria HospitalPekanbaru). The results show that: 1) Communication has a positive andsignificant Influence on the performance of the Nurses at Eria Hospital Pekanbaru,2) Organizational Culture has a positive and significant Influence on theperformance of the Nurses at Eria Hospital Pekanbaru, 3) Work environment hasa positive and significant Influence on the performance of the Nurses at EriaHospital Pekanbaru, 4) Communication, Organization Culture and WorkEnvironment has a positive and significant Influence on the performance of theNurses at Eria Hospital Pekanbaru. Keywords: Communication, Organizational Culture, Work Environment,Performance